Sistem Pemantauan dan Kontrol Smart Cat Room Berbasis Internet Of Things (IoT) - Ariansyah Sudarsono; Rahmi Hidayati; Uray Ristian (STMIK Budi Darma, 2023)
AbstractConditions of air temperature and air humidity as well as feeding for cats are some of the important elements difficult to monitor by cat keepers when they are not home. As a result, the cats’ feeding pattern and room conditions are not properly maintained. In this research, a system named smart cat room was built to monitor and control the air temperature, air humidity, food residue, and the amount of cat food. The types of cats in this research were Maine Coon, Bengal, and Persian. With this system, users can monitor and control the smart cat room through an Android-based application. The result of the testing of the smart cat room system had an average air temperature value for Maine Coon cats of 25.31°C and an air humidity value of Maine Coon cats is 62.90%. Average air temperature value for Bengal cats is 27.49°C and the air humidity value of Bengal cats is 62.33%. The average value of air temperature for Persian cats is 22.17°C and the air humidity value of Persia cats is 59.05%. According to the results, the smart cat room system shows that the average value of air temperature, air humidity are as according to the standards, with the cats’ skin and fur conditions inside the smart cat room well-maintained. Feeding can also be done at the right time and weight according to the type of cat in the Smart Cat Room